(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Comparative Analysis of Black Rice and White Rice Farming Income in Subak Bengkel, Tabanan. This research aims to analyze the comparison of income from black rice and white rice farming in Subak Bengkel Tabanan and the obstacles experienced by farmers in carrying out rice farming. The data analysis methods used in this research are quantitative and qualitative. The research results show that the revenue from black rice farming is Rp.20,104,000/ha/planting season, with total costs of Rp 3,350,575/ha/planting season, and the farming income obtained is Rp. 16,753,425/ha/planting season. Meanwhile, the income from white rice farming is Rp. 13,708,800/ha/planting season, with total costs incurred of Rp 3,301,172/ha/planting season, and the income obtained is Rp.10,407,628/ha/planting season. The results of the t test analysis show that there is a significant difference between the income from black rice and white rice farming. The obstacles experienced by farmers in carrying out farming are that farmers experience difficulties in determining the planting season, difficulties in obtaining water, farmers’ rice fields are flooded, problems with product marketing, as well as problems with pest attacks on rice plants resulting in farmers experiencing losses, including those caused by planthoppers, crabs, seed-eating birds, and attacks from rat pests.